2000
DOI: 10.1161/01.str.31.1.128
|View full text |Cite
|
Sign up to set email alerts
|

Angiographically Defined Collateral Circulation and Risk of Stroke in Patients With Severe Carotid Artery Stenosis

Abstract: Background and Purpose-Blood supply through collateral pathways improves regional cerebral blood flow and may protect against ischemic events. The effect of collaterals on the risk of stroke and transient ischemic attack (TIA), in the presence of angiographic severe internal carotid artery (ICA) stenosis, was assessed. Methods-Angiographic collateral filling through anterior communicating and posterior communicating arteries and retrograde filling through ophthalmic arteries were determined in all patients at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
246
1
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 345 publications
(262 citation statements)
references
References 29 publications
9
246
1
6
Order By: Relevance
“…Two studies, in patients with carotid artery disease, 37 also reported a lower prevalence of cerebral collateral circulation among the patients with hypertension. Yet, three other studies 9 found hypertension to be positively associated with the presence of CCs.…”
Section: Discussionmentioning
confidence: 92%
“…Two studies, in patients with carotid artery disease, 37 also reported a lower prevalence of cerebral collateral circulation among the patients with hypertension. Yet, three other studies 9 found hypertension to be positively associated with the presence of CCs.…”
Section: Discussionmentioning
confidence: 92%
“…In particular, patients with symptomatic ICA occlusion have deteriorated cerebral hemodynamics and metabolism (26). However, when the collaterals were demonstrated angiographically, the patients were shown to bear a lower risk of hemispheric stroke or transient ischemic attack (TIA) (29). MRA is a sensitive tool for assessing occlusive artery disease in stroke with a high concordance with perfusion abnormalities in the acute situation (30 -32).…”
Section: Discussionmentioning
confidence: 99%
“…Those patients with variants of the circle with efficient collateral circulation have a lower risk of transient ischemic attack and stroke than that of patients without such collaterals. 4,5 CT angiography (CTA) allows reliable non-invasive evaluation of the intracranial arteries. Moreover, CTA provides useful information about anatomical variations of cerebral circulation, with reported high sensitivity and specificity (81-90% and 93%, respectively), approaching the diagnostic accuracy of digital subtraction angiography.…”
Section: Introductionmentioning
confidence: 99%